Response of Different Level of Nitrogen and Phosphorus on Grain Yield, Oil Quality and Nutrient Uptake of Soybean (Bangladesh Journal of Scientific and Industrial Research, 2009)
A field experiment was conducted to find out the effect to different levels of nitrogen and phosphorus on yield, oil contents and quality and nutrient uptake of soybean. The maximum plant height and number of pod per plant were recorded by the application of 40kg N / ha. Single application of phosphorus also bring significant increased in oil content of soybean. Nitrogen, phosphorus, potash content of soybean seed and straw varied with different treatment of NP. Interaction showed oil content of soybean was influenced with increasing level of nitrogen and phosphorus. The percent of oil and yield of soybean were found maximized by the application of 40kg N / ha + 30kg P2O5 / ha. However, moisture, density, refractive index and peroxide value of soybean oil remain more or less same throughout the experiment. Key words: Nitrogen, Phosphorus, Oil quality, Nutrient content, Grain and Straw yield. DOI: 10.3329/bjsir.v44i2.3670 Bangladesh J. Sci. Ind. Res. 44(2), 187-192, 2009